1979
DOI: 10.1128/aac.15.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Thienamycin: New Beta-Lactam Antibiotic with Potent Broad-Spectrum Activity

Abstract: Thienamycin, a new beta-lactam antibiotic, exhibited potent, broad-spectrum activity in vitro against gram-negative bacilli and gram-positive cocci, including many isolates resistant to currently available antibiotics. All isolates were inhibited at concentrations les than or equal to 25 yg/ml, with the exception of 12% Ill., abstr. no. 228, 1976). This study was undertaken to confirm these observations and add data which compare this drug with carbenicillin, ticarcillin, and amoxicilhin, which are in current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 5 publications
0
18
1
Order By: Relevance
“…Cefoperazone achieved 50 and 90% inhibition at 25 and 50 ,tg/ml, respectively. DISCUSSION Earlier studies demonstrated that thienamycin is a potent antibiotic with a broad spectrum of activity (6,7). N-Formimidoyl thienamycin, a derivative of thienamycin, has been shown to be more stable, more active in vitro, and more effective for treatment of infections in mice (H. Kropp Chemother.…”
Section: Resultsmentioning
confidence: 99%
“…Cefoperazone achieved 50 and 90% inhibition at 25 and 50 ,tg/ml, respectively. DISCUSSION Earlier studies demonstrated that thienamycin is a potent antibiotic with a broad spectrum of activity (6,7). N-Formimidoyl thienamycin, a derivative of thienamycin, has been shown to be more stable, more active in vitro, and more effective for treatment of infections in mice (H. Kropp Chemother.…”
Section: Resultsmentioning
confidence: 99%
“…Thienamycin exhibits potent activity against a wide variety of aerobic and anaerobic bacteria (5,6). However, thienamycin also possesses considerable chemical instability, remaining active only within a relatively narrow range of pH, temperature, and antibiotic concentration (2).…”
Section: Mk0787 (N-formimidoyl Thienamycin) Is Amentioning
confidence: 99%
“…In vitro studies of imipenem have demonstrated a broad spectrum of antibacterial activity (25,28) which includes both ,-lactamand aminoglycoside-resistant pathogens (10,14,22,26). In addition, the drug has been shown to be resistant to multiple 3-lactamases (3,21) and to possess marked in vitro activity against methicillin-resistant staphylococci (14,26,29).…”
mentioning
confidence: 99%